LNG mass flow measurement uncertainty reduction using calculated Young's modulus and Poisson's ratio for Coriolis flowmeters. (January 2022) - Wu, Thomas Y.; Kenbar, Asaad
Highlights: Young's modulus of a CMF is estimated from LNG density and bending frequency, with uncertainty of 0.071%. LNG mass flow measurement uncertainty of a straight-tube CMF could be reduced from 0.50% to 0.20% (k = 2). Poisson's ratio of tube can be calculated from torsional and bending frequency with uncertainty of 0.14%. Mass flow factor for a U-tube CMF can be corrected using calculated Poisson's ratio. LNG mass flow uncertainty of a U-tube CMF could be reduced to 0.24% (k = 2). Abstract: We have proposed new methods to reduce the LNG mass flow measurement uncertainty using a Coriolis mass flowmeters (CMF). Since the uncertainty in the corrected Young's modulus of meter tube is the dominating contribution factor, it is proposed to derive the Young's modulus at LNG temperature using the calculated LNG density and the natural bending frequency measurement. The expanded uncertainty of the calculated Young's modulus is evaluated to be 0.071%, which will enable the LNG mass flow measurement uncertainty of a straight-tube CMF to be reduced from 0.50% to 0.20% ( k =2). This approach has the potential to provide more accurate LNG mass flow measurement in comparison to conventional methods which use the corrected Young's modulus at LNG temperature. We have analysed the error in flow measurement using a U-tube CMF. An extra mass flow factor is shown to be the dominating mass flow measurement uncertainty factor due to the high uncertainty in the measured Poisson's ratio of the tube. A new method is proposed to calculate the Poisson's ratio from the torsional frequency and bending frequency measurements, with expanded uncertainty of 0.14%, 13 times lower than that of the measured values. The LNG mass flow measurement uncertainty of a U-tube CMF is estimated to be to 0.24% ( k =2) using the calculated Poisson's ratio and Young's modulus. Our theoretical analysis shows that accurate estimation of Young's modulus and Poisson's ratio can significantly reduce the LNG mass flow measurement uncertainty using a CMF.